Pengaruh Penerapan Metode PQ4R (Preview, Question, Read, Reflect, Recite, Review) terhadap Keterampilan Membaca Pemahaman Peserta Didik - Elvia, Elvira; Halimah, Andi; Syahruddin (Faculty of Tarbiyah and Teacher Training, 2024)
This study aims to determine the effect of implementing the PQ4R method on the reading comprehension skills of class V students of MI Madani Alauddin. This study is a quantitative study with a quasi-experimental design. The population in this study consisted of classes V A and V B, with 60 students of MI Madani Alauddin. The sampling technique used was saturated sampling. The research instrument was a reading comprehension ability test. The data obtained were analyzed using descriptive and inferential statistical analysis. The results of the analysis showed that the reading comprehension skills of students in classes that did not apply the PQ4R method were in the moderate category, while the reading comprehension skills of students in classes that applied the PQ4R method were in the high category. The results of the analysis also showed that the application of the PQ4R method had a positive effect on the reading comprehension skills of class V students of MI Madani Alauddin. The implications of the research based on the study results indicate that the PQ4R method affects reading comprehension skills. Therefore, it is recommended that schools, especially elementary school teachers, use the PQ4R method in order to achieve effective learning.